STRATEGI PT. PERTAMINA HULU ROKAN DALAM MELAKSANAKAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) TUJUAN KE-13 DI INDONESIA - Afifah, Nurul; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The Sustainable Development Goals (SDGs) are a global framework for sustainable development that has been agreed upon by the United Nations member states to be achieved by 2030. Its success requires contributions from various stakeholders, including the business sector. PT Pertamina Hulu Rokan (PHR), as a company in the oil and gas industry, plays a role in mitigating climate change, which is the focus of SDG Goal 13. This research examines the implementation of PT PHR in fulfilling SDG Goal 13 in efforts to address climate change. This study uses green theory with a state-level analysis. Green theory explains that an actor's participation in implementing sustainable development is influenced by ecological awareness and environmental responsibility, as emphasized in green theory. This theory highlights the importance of balancing economic interests and environmental preservation while rejecting the dominance of anthropocentric approaches that focus solely on human interests. The research employs a qualitative method with an explanatory approach, using data collection techniques through literature review, including the analysis of annual reports, academic journals, previous research, and other official sources. The research findings show that PT PHR implements SDG Goal 13 through its sustainability strategy, TJSL (Corporate Social Responsibility) initiatives, which include the utilization of flare gas, development of renewable energy, waste bank programs, waste management, mangrove conservation, construction of constructed wetlands, forest preservation, calculation of greenhouse gas emissions, and risk management. Keywords: PT Pertamina Hulu Rokan, SDGs, Climate Change, Sustainability strategy.